UPAYA MENINGKATKAN MINAT BACA SISWA SD KELAS III DENGAN MENGGUNAKAN ALAT PERAGA BERGAMBAR DI SD NEGERI MACCINI II KOTA MAKASSAR - Gunadi Adi Putra Yunus (PEDAGOGIK, 2014)
The objective of the research was to describe the third grade students’ interest in reading. The  research  design  applied  collaborative  classroom  action  research.    The  subjects involved the  Third  Graders  of Maccini  Public  School  II  in  Makassar  City. The  data collected through observation, interviews, and documentation. The conclusion of the research showed that student’s interest in reading through teaching   reading activities tends to increase.The objective of this research is to find out if the picture demonstration tool could increasethe student’s reading interest in students of grade III of Maccini II State Elementary School Makassar City. This research was in-class action research conducted in 2 cycles. The subjects of this research were students of grade III of Maccini II State Elementary School Makassar City in the second semester of the academic year of 2007/2008. The data of this research was collected through observation, interviews, and documentation, and analyzed collaboratively through three interactive model activity plots, i.e. data reduction, data explanation, verification and drawing conclusion.The actions conducted in this research result in some positive changes in the activities done by the students in reading. These changes are indicated by the increase  of thepercentage of students which are conducting reading activity. Before the conduction, thestudents who were enthusiastic about reading were only 41.02%, which, after Cycle I increased to 79.49%; and in the end of Cycle II it increased to 97.43%. In terms of the students’ activity in comprehending the text and story through intensive reading, it increased from 41.15% (early condition), to 71.79 (end of Cycle I), and increased to94.87% (end  of  Cycle II). The  students’  activity in expressing their ideas  orally  and appropriately increased from 30.77% (early condition), to 69.23% (end of Cycle I), andincreased to 87.18 % (end of Cycle II). The activity of students in scrupulous readingincreased from 48.72% (early condition), to 76.92% (end of Cycle I), and to 94.87% (end of Cycle II). The activity of students in individual and group enjoyable reading increased from 33.33% (early condition), to 69.23% (end of Cycle II) and to 94.87% (end of Cycle II). The last activity, completing sentences according to the meanings given on figures, increased from 28.20% (early condition), to 76.92%) (end of Cycle II), and to 97.43% (end of Cycle II). The average percentage of the given activities (6 indicators of activities) increased from 37.20% (early condition), to 73.93% (end of Cycle I), and to 94.44% (end of Cycle II). Thus, in all the activities there was a gain percentage of 36.73% in Cycle I and 55.22% in Cycle II. Keywords: students’ reading interest, Picture Demonstration Tool